"Nummer Elf" - Daum, P. A. (Paul Adriaan), 1849-1898 (Salt Lake City, UT : Project Gutenberg, 2023)
"Nummer Elf" by P. A. Daum is a novel written in the late 19th century. The story introduces Lena Bruce, a young girl burdened by the responsibilities of caring for her asthmatic mother and managing a chaotic household. Through Lena$1 (Bs perspective, we get a glimpse of her life, her family dynamics, and the pressures of societal expectations, particularly surrounding marriage. The opening of the story sets the stage for Lena's daily struggles and highlights her character as both dutiful and weary. It begins with a vivid scene of Lena late at night, reading quietly while tending to her ailing mother. As the story unfolds, we learn about her family's dynamics, including her father$1 (Bs indifference and her brother$1 (Bs carefree nature compared to her serious disposition. Meanwhile, George Vermey, a man with his own contrasting life challenges and romantic intentions toward Lena, is introduced, along with his internal conflicts about marriage. The interactions between Lena, her family, and Vermey suggest a central tension regarding societal roles and personal desires that will likely propel the narrative forward. (This is an automatically generated summary.)s
Release date is 2023-02-16
Jeroen Hellingman and the Online Distributed Proofreading Team at https://www.pgdp.net/ for Project Gutenberg (This book was produced from scanned images of public domain material from the Google Books project.)
Keywords: Dutch fiction -- 19th century